Significance of lymph node involvement in local recurrence of colorectal cancer. Issue 4 (22nd July 2019) - Dumont, Frédéric; Muñoz, Miguel A.; De Franco, Valéria; Wernert, Romuald; Verriele, Valérie; Heyman, Marie‐Françoise; Kerdraon, Olivier; Capitain, Olivier; Guerin‐Meyer, Véronique; Raimbourg, Judith; Senellart, Hélène; Hiret, Sandrine; et al.
Abstract: Background: There are few data on lymphatic spread concomitant to local recurrence (LR) of colorectal cancer (CRC). The objectives of this study were to determine variables associated with lymphatic spread, to analyze the distribution of LN+, and understand the underlying mechanisms. Methods: A total of 76 patients underwent resection of LR of CRC between January 2007 and December 2018 at Institut cancérologique de l'Ouest and were retrospectively reviewed. Results: Twenty‐five (32.9%) patients had lymph node (LN) involvement with LR. Lymphatics from the mesocolon‐rectum and aorto‐iliac compartments were involved in 21%, 20.3% and 18.1%, 20.3% for pelvic and retroperitoneal LRs, respectively. In multivariate analysis, the only predictive factor for LN invasion (LN+) was a primary positive LN status (odds ratio, 5.3; P = .007). Despite a trend toward a worse median overall survival in the LN+ group, the difference was not significant in comparison with the LN− group (46 vs. 57 months; P = 0.31) or with the LN− plus LN not assessed groups (46 months vs not reached; P = .07). Conclusions: LN invasion with LR from CRC is a frequent occurrence without significant impact on survival. The only predictive factor is a primary positive nodal status.